THE POWER OF MAMA-MAMA: PENDEKATAN GENDER DALAM EDUKASI PENGELOLAAN SAMPAH KELUARGA DI KAWASAN PA-DAT PENDUDUK MEDAN TEMBUNG - Nasution, Edwin Sugesti; Lazuardi, Dedy; Wahyuni, Putri (Smart Education, 2025)
Abstract: Waste management in Medan Tembung faces complex challenges due to high population density, limited infrastructure, and low community participation. This community service initiative aims to empower mothers as agents of change through a gender-based approach. The methods used include: (1) soscialization of Regional Regulation No 6 of 2015 (2) practical training on waste sorting and household-scale composting, (3) mentoring by environmental cadres, and (4) a community-based reward system. The results show significant improvement in women's participation (85% of participants), with 72% of households consistently practicing waste sorting. The program also improves comprehension and awareness about household waste separation. Key findings reveal that approaches leveraging women's social networks (PKK, savings groups) and local value integration are more effective than mere regulatory socialization. This initiative demonstrates that empowering mothers can be a sustainable strategy for family-based waste management in densely populated areas. Keywords: women's empowerment; household waste management; gender approach; Medan Tembung; circular economy